Public Procurement in Albania, Germany, Macedonia and Kosovo - Salianji, Ervin (European Journal of Multidisciplinary Studies, 2017)
The public procurements is a developed field in the countries which had blooming economic development trends. It is a very important field for the governments as every government is a buyer of goods, services and performance of works. During the last years in all the countries public procurement occupied an important space as through it the expenses of public money is performed. This trend of development during this period is more emphasized especially in the countries which had a transition from the planned economics to market economy. For the eastern and central Europe public procurement these last 20 years was a new term as the economy of these countries was planned and centralized.
Keywords: Public Procurement Albania, Germany, Macedonia Kosovo